The Role of Gut Microbiota in Different Types of Physical Activity and Their Intensity: Systematic Review and Meta-Analysis - Tehreema Ghaffar; Francesca Ubaldi; Veronica Volpini; Federica Valeriani; Vincenzo Romano Spica (MDPI AG, 2024)
Background. Intense exercise during training requires dietary modulation to support health and performance and differs in different types of activities. Diet, supplementation with prebiotics and probiotics, and, more recently, even physical activity can potentially improve health outcomes by modifying and protecting the gut microbiota. A systematic review and meta-analysis were conducted to investigate the modulation of gut microbiota in different types and intensities of physical activity and different lifestyles of athletes. Methods. The systematic review and meta-analysis were conducted according to the PRISMA guidelines, and the protocol was registered in PROSPERO (CRD42024500826). Results. Out of 1318 studies, only 10 met the criteria for inclusion in the meta-analysis. The pilot study's meta-regression analysis highlights the role of type and intensity of exercise in changing the B/B (Bacillota/Bacteroidota) ratio (p = 0.001). Conclusions. As gut training becomes more popular among athletes, it is necessary to map interactions between microbiota and different types of physical activity, personalized diets, physical activities, and ergogenic supplements to enhance performance and athletic wellness.